TEACHER AND STUDENTS’ PERCEPTIONS TOWARD THE USE OF STUDENTS’ L1 IN EFL CLASSROOM - Lailah Isrofatun Nahdiah (Universitas Pendidikan Indonesia, 2022)
This study reports the Indonesian language use as a mother tongue (L1) in an EFL classroom in a middle school setting. The goals are to investigate the realization use of L1 and examine the teacher and students’ perceptions. A case study method is used in this study. The data are obtained through triangulations: classroom observation, students’ questionnaires, and teacher and students’ interviews. Thirty-two students and one teacher are involved. The basic frameworks in this study depend on Auerbach's (1993), Schweers's (1999), and Cook's (2001) frameworks. The finding shows that L1 is reasonably needed as a facilitator in EFL classroom. The benefits of L1 use are: for repeating unclear statements, asking for a translation, explaining grammar, checking for understanding, gaining attention, and making jokes. The teacher and the students show positive attitudes toward the use of L1